2013
DOI: 10.1509/jm.11.0222
|View full text |Cite
|
Sign up to set email alerts
|

To Buy or Not to Buy: Consumers’ Demand Response Patterns for Healthy versus Unhealthy Food

Abstract: The authors integrate research on impulsivity from the psychology area with standard economic theories of consumer demand to make novel predictions about the effects of market price changes on consumers’ food consumption behavior. The results from multiple studies confirm that consumers exhibit undesirable asymmetric patterns of demand sensitivity to price changes for healthy and unhealthy food. For healthy food, demand sensitivity is greater for a price increase than for a price decrease. For unhealthy food, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 49 publications
6
62
0
Order By: Relevance
“…The emotive imagery and associated desire for unhealthy products (e.g., cookies, doughnuts, cakes) trigger impulsive purchase decisions (Loewenstein 1996;Shiv and Fedorikhin 1999;Thomas et al 2011;Wertenbroch 1998). This idea is in line with marketing scholars' findings that the impulse to consume unhealthy food is stronger than that to consume healthy food (Talukdar and Lindsey 2013). Therefore, unhealthy food poses a greater need for self-control than healthy food.…”
Section: Theoretical Development and Hypothesessupporting
confidence: 77%
“…The emotive imagery and associated desire for unhealthy products (e.g., cookies, doughnuts, cakes) trigger impulsive purchase decisions (Loewenstein 1996;Shiv and Fedorikhin 1999;Thomas et al 2011;Wertenbroch 1998). This idea is in line with marketing scholars' findings that the impulse to consume unhealthy food is stronger than that to consume healthy food (Talukdar and Lindsey 2013). Therefore, unhealthy food poses a greater need for self-control than healthy food.…”
Section: Theoretical Development and Hypothesessupporting
confidence: 77%
“…Supermarket scanner and experimental studies reveal consumers' demand sensitivity for healthy foods is greater for a price increase than a decrease, but the opposite is true for unhealthy foods (Talukdar and Lindsey 2013). This suggests that consumers are more responsive to price promotions when offered on unhealthy foods than when more nutritious options are placed on deal.…”
Section: Story and Stang 2006)mentioning
confidence: 99%
“…In addition to these contexts, we argue that consumers' asymmetric demand patterns are also category dependent (Talukdar and Lindsey, 2013;Bell and Lattin, 2000). Food categories differ across healthiness level and palatability, which have different impacts on the 13 demand pattern.…”
Section: Asymmetric Demand Patternsmentioning
confidence: 92%
“…In this pattern, consumers are more sensitive to a fall in price than to a rise in price relative to the last purchase. Some prior studies have found empirical evidence to support this pattern, indicating that this pattern is applicable if consumers exert brand loyalty towards a brand (Krishnamurthi et al, 1992), are unfamiliar with the promotion frequency or the product's own price volatility (Han et al, 2001;Müller and Ray, 2007;Pauwels et al, 2007), and/or are less likely to "discount" price promotion (Gupta and Cooper, 1992, p.403); or if consumers exhibit a natural impulse to "overconsume" unhealthy food (Talukdar and Lindsey, 2013).…”
Section: Desirable and Undesirable Demand Patternsmentioning
confidence: 99%
See 1 more Smart Citation